Financial Health of Local Governments and Its Connection with ESG - Bohdalová, Mária; Kukučka, Andrej (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The chapter examines the relationship between ESG factors and the credit risk of Slovak municipalities. We assume that the financial profile of a municipality cannot be fully understood from its financial statements alone, and that the environment in which it operates is an equally important part of the assessment. Our dataset includes four financial indicators, namely debt, liquidity, economic margin and debt service, the unemployment rate as a social indicator and three environmental air quality indicators, namely PM10, PM2.5 and NO2. Factor analysis identifies the hidden structure of relationships among variables and extracts four components that explain 81.5% of the total variability. The first component links the concentrations of PM10 and PM2.5 particulate matter to municipalities' indebtedness, indicating a common dimension of environmental burden and financial risk. Discriminant analysis classifies municipalities into two groups: those with problem debt and those without. The key variables differentiating the groups are economic margin, liquidity and debt service. The structural matrix also shows that the environmental variables PM2.5 and NO2 exhibit a stronger direct connection with the discriminant function than most financial variables, confirming their additional information value.